Charitable Donations on the Street of Sungai Tunjang Village, Cerbon District, Barito Kuala District 2000-2022 - Wahdah, Wahdah; Rochgiyanti, Rochgiyanti; Yahya, Daud (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The religious activities allow them to fulfill the development funds that have become a mechanism for a running job field, which should be purely for common interests. The purpose of the research is to understand the background and impact of the contribution of religious activities on the road of Sungai Tunjang Village, Cerbon District, Barito Kuala Regency, in the years 2000-2022. This article uses the historical method, consisting of heuristics, criticism, interpretation and historiography. The research results show that since the year 2000, contributions have been found in the development of mosques/musholas on the road. The contributions occurred because the funds received from the community's collection for each house for the construction of musholas in Sungai Tunjang Village were insufficient. The positive impact is to raise public awareness that the search for contributions on the highway should not be misused for personal interests. The negative impact is to create a sense of resentment and difficulty due to the lack of funds for implementation, while personal funds are not available and slow down the journey for those who do not understand the existence of religious activities.